Between Massachusetts and Catalonia: Constitutional mutations and democratic dysfunctions - Clavero, Bartolomé (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
What comes next is the revised transcription of an oral speech addressing the predicament aroused by arguable mismatches between democracy and constitutionalism (in the sense of rule of rights) in constituting multilevel polities within multinational milieus. Through the comparison of constitutional mutations of Spain and United States of America, this essay highlights the dysfunction of democracy (in the sense of direct appeal to nationwide constituencies) regarding the guarantee and promotion of not just individual but also collective rights, such as those of nations which do not constitute States by themselves.
Keywords: Constitutional mutations; American constitutionalism; Spanish constitutionalism; separation of powers; constituent plebiscites; Multinational State